Preventing Stunting Through Digital Family Empowerment: A Thematic Literature Review - Syamsir, Syamikar Baridwan; Setiawan, Agus; Kurwiyah, Neneng; Naralia, T. Widya; Supriyatno, Heru; Mar'ah, Novya Ashlahatul (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: The increasing prevalence of stunting and its associated morbidities highlight the need for effective prevention measures. Digital-based family empowerment interventions have been identified as a promising approach to prevent stunting. This study aims to investigate various types of digital-based family empowerment interventions in preventing stunting and optimizing child growth. Method: It is a thematic literature review using a semi-structured search approach with predefined keywords in four major databases, namely Scopus, PubMed, ProQuest, and Google Scholar. The research applies a systematic research method with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines and sets search boundaries using the PICO (Population/Problem, Intervention, Comparison, Outcome) approach. Three search criteria include digital-based family empowerment interventions for stunting prevention, articles published within the last five years, and written in English or Indonesian. Result: From the search, nine articles were selected, forming three main themes: (1) digital-based child growth and development monitoring programs in preventing stunting; (2) digital-based health education programs for stunting prevention; and (3) digital-based nutrition counseling programs in preventing stunting. Conclusion: Digital-based family empowerment interventions have proven to be effective in stunting prevention efforts. With a better understanding of these interventions, it is hoped that knowledge and skills in preventing stunting and optimizing child growth can be enhanced. The role of nurses can be pivotal in integrating technology into family education.